Tgm1-like transglutaminases in tilapia (Oreochromis mossambicus). - Sandra I Rodriguez Cruz; Marjorie A Phillips; Dietmar Kültz; Robert H Rice (PLoS ONE, 2017)
Among the adaptations of aquatic species during evolution of terrestrial tetrapods was the development of an epidermis preventing desiccation. In present day mammals, keratinocytes of the epidermis, using a membrane-bound transglutaminase (Tgm1), accomplish this function by synthesizing a scaffold of cross-linked protein to which a lipid envelope is attached. This study characterizes the abilities of two homologous transglutaminase isozymes in the teleost fish tilapia to form cross-linked protein structures and their expression in certain tissues. Results indicate they are capable of membrane localization and of generating cellular structures resistant to detergent solubilization. They are both expressed in epithelial cells of the lip, buccal cavity and tips of gill filaments. Adaptation of transglutaminase use in evolution of terrestrial keratinocytes evidently involved refinements in tissue expression, access to suitable substrate proteins and activation of cross-linking during terminal differentiation.